Application of Cold Drink in Post Operation Nausea and Vomiting (PONV) Appendectomy Cases in Lubuklinggau - Jhon Feri; Wella Juartika; Eva Oktaviani; Derison Marsivova Bakara; Gunardi Pome (Babali Nursing Research, 2023)
Introducition: Post Operative Nausea and Vomiting (PONV) is one of the most common complications after surgery, it affects the patient's time recovery and causes discomfort including: pain, electrolyte imbalance, dehydration, risk of aspiration, risk of wound opening and bleeding. The purpose of this study was to see a decrease in postoperative nausea and vomiting scores. Methods: The research design used was quasi-experimental with 2 pre-post test groups. The sample in this study were 42 people with a total of 21 people in the intervention group and 21 people in the control group. The variable in the study looked at the score of postoperative nausea and vomiting. Instruments used by Rhodes INVR. Data analysis used SPSS test with Mann-Withney. Results: There was a significant difference in respondents' scores (p-value = 0.000, < 0.05). In addition, it showed a difference in the average score of the test between the control group (19.00) and the invention group (3.00), with an average difference of 16.00. Conculsion: The application of cold drinks in PONV has proven to be more effective in reducing vomiting nausea. This method can be used as an alternative method in meeting the needs of body fluids when getting complaints of nausea vomiting. To achieve the goal of preventing the occurrence of the impact of vomiting nausea such as preventing dehydration.